Bacterial Materials: Applications of Natural and Modified Biofilms. Issue 21 (10th October 2021) - Hayta, Elif N.; Ertelt, Marvin J.; Kretschmer, Martin; Lieleg, Oliver
Abstract: Over millennia, bacteria have developed clever strategies to build biopolymer‐based communities in which they can survive even extremely challenging conditions. Such bacterial biofilms come with a broad range of fascinating material properties that—in settings such as medicine, food production, or other areas of industry—make it difficult to remove or inactivate them: they can stick to many surfaces, repel water and oils, and can even transport electrons. Inspired by the outstanding versatility and sturdiness of such bacterial biofilms, material scientists have set out to harness those properties and to create bacterial materials for different applications. However, as the range of technological applications employing biofilms keeps expanding, improved material properties or broader functionalities are desired. Here, such attempts where materials with improved properties were created by making use of either natural or modified bacterial biofilms are reviewed. The areas in which those bacterial materials may be used range from agriculture and (environmental) biotechnology over biomedical and electrical engineering to construction engineering. Abstract : Natural and modified biofilms that can be employed in agriculture, (environmental) biotechnology, medicine, electricity generation, and civil engineering are reviewed.